Nomimicins B–D, new tetronate-class polyketides from a marine-derived actinomycete of the genus Actinomadura - Zhang, Zhiwei; Zhou, Tao; Yang, Taehui; Fukaya, Keisuke; Harunari, Enjuro; Saito, Shun; Yamada, Katsuhisa; Imada, Chiaki; Urabe, Daisuke; Igarashi, Yasuhiro (Beilstein Journal of Organic Chemistry, 2021)
Three new tetronate-class polyketides, nomimicins B, C, and D, along with nomimicin, hereafter named nomimicin A, were isolated from the culture extract of Actinomadura sp. AKA43 collected from floating particles in the deep-sea water of Sagami Bay, Japan. The structures of nomimicins B, C, and D were elucidated through the interpretation of NMR and MS analytical data, and the absolute configuration was determined by combination of NOESY/ROESY and ECD analyses. Nomimicins B, C, and D showed antimicrobial activity against Gram-positive bacteria, Kocuria rhizophila and Bacillus subtilis, with MIC values in the range of 6.5 to 12.5 μg/mL. Nomimicins B and C also displayed cytotoxicity against P388 murine leukemia cells with IC50 values of 33 and 89 μM, respectively.
Keywords: Actinomadura; nomimicin; polyketide; spirotetronate

(untitled) - Bérdy, J. (J. Antibiot., 2005)

(untitled) - Lam, K. S. (Curr. Opin. Microbiol., 2006)

(untitled) - Sayed, A. M.; Hassan, M. H. A.; Alhadrami, H. A.; Hassan, H. M.; Goodfellow, M.; Rateb, M. E. (J. Appl. Microbiol., 2020)

(untitled) - ul Hassan, S. S.; Shaikh, A. L. (Biomed. Pharmacother., 2017)

(untitled) - Manivasagan, P.; Venkatesan, J.; Sivakumar, K.; Kim, S.-K. (Microbiol. Res., 2014)

(untitled) - Blunt, J. W.; Copp, B. R.; Keyzers, R. A.; Munro, M. H. G.; Prinsep, M. R. (Nat. Prod. Rep., 2017)

(untitled) - Abdelmohsen, U. R.; Bayer, K.; Hentschel, U. (Nat. Prod. Rep., 2014)

(untitled) - Wang, C.; Lu, Y.; Cao, S. (Arch. Pharmacal Res., 2020)

(untitled) - Furumai, T.; Eto, K.; Sasaki, T.; Higuchi, H.; Onaka, H.; Saito, N.; Fujita, T.; Naoki, H.; Igarashi, Y. (J. Antibiot., 2002)

(untitled) - Igarashi, Y.; Ikeda, M.; Miyanaga, S.; Kasai, H.; Shizuri, Y.; Matsuura, N. (J. Antibiot., 2015)

(untitled) - Karim, M. R. U.; In, Y.; Zhou, T.; Harunari, E.; Oku, N.; Igarashi, Y. (Org. Lett., 2021)

(untitled) - Yang, T.; Yamada, K.; Nakayama, J.; Igarashi, Y.; Terahara, T.; Kobayashi, T.; Imada, C. (Deep Ocean Water Res., 2019)

(untitled) - Yang, T.; Yamada, K.; Zhou, T.; Harunari, E.; Igarashi, Y.; Terahara, T.; Kobayashi, T.; Imada, C. (J. Antibiot., 2019)

(untitled) - Igarashi, Y.; Matsuyuki, Y.; Yamada, M.; Fujihara, N.; Harunari, E.; Oku, N.; Karim, M. R. U.; Yang, T.; Yamada, K.; Imada, C.; Fukaya, K.; Urabe, D. (J. Org. Chem., 2021)

(untitled) - Igarashi, Y.; Iida, T.; Oku, N.; Watanabe, H.; Furihata, K.; Miyanouchi, K. (J. Antibiot., 2012)

(untitled) - Terui, Y.; Sakazaki, R.; Shoji, J. (J. Antibiot., 1990)

(untitled) - Keller-Juslén, C.; King, H. D.; Kuhn, M.; Loosli, H. R.; Pache, W.; Petcher, T. J.; Weber, H. P.; von Wartburg, A. (J. Antibiot., 1982)

(untitled) - Hatsu, M.; Sasaki, T.; Miyadoh, S.; Watabe, H.; Takeuchi, Y.; Kodama, Y.; Orikasa, Y.; Kajii, K.; Shomura, T.; Yamamoto, H.; Sezaki, M.; Inouye, S.; et al. (J. Antibiot., 1990)

(untitled) - Igarashi, Y.; Matsuoka, N.; In, Y.; Kataura, T.; Tashiro, E.; Saiki, I.; Sudoh, Y.; Duangmal, K.; Thamchaipenet, A. (Org. Lett., 2017)

(untitled) - Hashimoto, T.; Hashimoto, J.; Teruya, K.; Hirano, T.; Shin-ya, K.; Ikeda, H.; Liu, H.-w.; Nishiyama, M.; Kuzuyama, T. (J. Am. Chem. Soc., 2015)

(untitled) - Lacoske, M. H.; Theodorakis, E. A. (J. Nat. Prod., 2015)

(untitled) - Braddock, A. A.; Theodorakis, E. A. (Mar. Drugs, 2019)

(untitled) - Tomita, F.; Tamaoki, T.; Shirahata, K.; Kasai, M.; Morimoto, M.; Ohkubo, S.; Mineura, K.; Ishii, S. (J. Antibiot., 1980)

(untitled) - Mallams, A. K.; Puar, M. S.; Rossman, R. R.; McPhail, A. T.; Macfarlane, R. D. (J. Am. Chem. Soc., 1981)

(untitled) - Zhang, H.; White-Phillip, J. A.; Melançon, C. E., III; Kwon, H.-j.; Yu, W.-l.; Liu, H.-w. (J. Am. Chem. Soc., 2007)

(untitled) - Jeon, B.-s.; Wang, S.-A.; Ruszczycky, M. W.; Liu, H.-w. (Chem. Rev., 2017)

MacroModel (Schrödinger, LLC, 2020)

Gaussian 16, Revision C.01 (Gaussian, Inc., 2016)

(untitled) - Karim, M. R. U.; Harunari, E.; Oku, N.; Akasaka, K.; Igarashi, Y. (J. Nat. Prod., 2020)